Pengaruh Variabel Moneter Dalam Negeri Dan Luar Terhadap Nilai Tukar Rupiah - Mustafa, Fahdilla; Nurjannah Nurjannah; Rinaldi Syahputra (Universitas 45 Surabaya, 2023)
This study aims to determine the effect of domestic inflation, foreign inflation, BI rate and fed rate on the rupiah exchange rate. The observed data is data for the period 2000-2022. Methods of data analysis using multiple linear regression analysis, t test, F test, and test the coefficient of determination. The regression equation in this study is Y = 5.885 - 0.29X1 + 0.156X2 + 0.229X3 - 0.016X4. Domestic inflation has a significant effect on the rupiah exchange rate, where from the t test the t sig value is obtained. 0.027 <0.05. Foreign inflation has a significant effect on the rupiah exchange rate, where from the t test the t sig value is obtained. 0.031 <0.05. The BI rate has a significant effect on the rupiah exchange rate, where from the t test the t sig value is obtained. 0.037 <0.05. Fed rate has a significant effect on the rupiah exchange rate, where from the t test the t sig value is obtained. 0.042 <0.05. Domestic inflation, foreign inflation, the BI rate and the fed rate simultaneously have a significant effect on the rupiah exchange rate, where the t test obtains the t sig value. 0.042 <0.05. Based on the test of the coefficient of determination, it is known that the variables of domestic inflation, foreign inflation, BI rate and fed rate affect the rupiah exchange rate by 59.1 percent, while the remaining 40.9 percent are influenced by other variables outside this research model..